2018
DOI: 10.24252/al-kimia.v6i2.6316
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic and Flavonoid Content, and Antioxidant Capacity of Red Ginger (Zingiber officinale var. Rubrum) Ethanolic Extract and Fraction

Abstract: Determination of total phenolic, total flavonoid, and antioxidant capacity of ethanolic extract and fractions from red ginger (Zingiber officinale var. Rubrum) has been done. Red gingers contain the highest oleoresins among other ginger varieties. Oleoresins are component that had the most responsibility for pharmacological effect of red ginger, one of them is as antioxidant. Phenolic and flavonoid are highly contributing to the antioxidant effect of red ginger. The aim of this research is to determine the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Previous research also stated the largest total flavonoids were from: ethyl acetate> 50% ethanol> butanol> hexane> water (Thavamoney et al, 2018). (Pratoko et al, 2018) also showed that the highest total flavonoid content obtained from ethyl acetate fraction of Z. officinale was 46.6 ± 1.8 mg QE/g extract while the one from hexane fraction was 26.1 ± 1.7 mg QE/g extract. Total flavonoid content, respectively from the largest: ethyl acetate> ethanol> n-hexane.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous research also stated the largest total flavonoids were from: ethyl acetate> 50% ethanol> butanol> hexane> water (Thavamoney et al, 2018). (Pratoko et al, 2018) also showed that the highest total flavonoid content obtained from ethyl acetate fraction of Z. officinale was 46.6 ± 1.8 mg QE/g extract while the one from hexane fraction was 26.1 ± 1.7 mg QE/g extract. Total flavonoid content, respectively from the largest: ethyl acetate> ethanol> n-hexane.…”
Section: Resultsmentioning
confidence: 78%
“…This result is in line with Ali et al ( 2018) who stated that total flavonoid content of chloroform-methanol (CM) extract from Z. officinale's was 40.25 ± 0.21 mg QE /gram. Pratoko et al (2018) also found that total flavonoid content from ethyl acetate extract of Z. officinale rhizome was 46.6 ± 1.8 mg QE/g. These results corroborate the statement about the high total flavonoid content of Z. officinale rhizome.…”
Section: Resultsmentioning
confidence: 84%
“…Senyawa fenolat merupakan senyawa yang bersifat polar (Apak et al, 2007). Struktur senyawa fenolat mempunyai tail hidrokarbon yang cukup panjang sehingga menyebabkan senyawa fenolat dalam jahe merah memiliki polaritas yang rendah (Siswandono et al, 2000;Pratoko et al, 2018).…”
Section: Hasil Dan Pembahasan Kandungan Senyawa Fenol Dan Flavonoidunclassified
“…Nilai IC50, yang semakin rendah menunjukkan semakin tinggi aktivitas antioksidannya (Badarinath et al, 2010). Hasil penelitian lain juga menunjukkan bahwa fraksi etil asetat ekstrak jahe merah merupakan fraksi yang mempunyai aktivitas antioksidan paling kuat (Suciyanti et al, 2017;Pratoko et al, 2018). Kaban et al (2016) menyatakan bahwa fraksi etil asetat ekstrak jahe merah mempunyai nilai IC50 yang lebih rendah dibandingkan dengan ekstrak ataupun fraksi lainnya.…”
Section: Aktivitas Antioksidanunclassified
“…The Indonesian population has historically used red ginger as a remedy for colds and back discomfort (FROTI 2017). This plant exhibits a range of pharmacological properties, including analgesic, wound healing, antibacterial, and antioxidant effects (Agusmawanti 2016;Febriani et al 2018;Pratoko et al 2018;Saptiwi et al 2018).…”
Section: Introductionmentioning
confidence: 99%